Efeito inibidor do tungstato de sódio e da amoxicilina em solução e em filmes de acetato de celulose na corrosão da liga de aço-carbono AISI 1020 em NaCl 0,05 mol/L - Scholant, Camila Monteiro (2014)
This study aimed to evaluate the sodium tungstate (Na2WO4) and amoxicillin as corrosion inhibitors for carbon steel alloy AISI 1020 added to a medium containing 0.05 mol/L sodium chloride (NaCl). Moreover, to evaluate the effect of these inhibitors when inserted in a film of cellulose acetate. The study consisted of exposing the metal in the proposed environment, in the absence and presence of 0.005, 0.01 and 0.07 mol/L of Na2WO4 and/or 1000, 2000 and 3000 ppm of amoxicillin or not inserted into films 5 % and 10 % cellulose acetate. Electrochemical techniques for monitoring the open circuit potential (PCO), electrochemical impedance spectroscopy (EIS) and anodic polarization were employed. All experiments were performed at room temperature and aerated environment. As for the proposed objectives can be concluded that: 1) PCO measures for the different concentrations of Na2WO4 showed displacement of the potential (E) towards more positive values during the 7 days of immersion in NaCl mainly to 0.07 mol/L Na2WO4 with E = - 0.407 V on day 7, indicating an inhibitory behavior. For different concentrations of amoxicillin potential values showed no significant variation as in 1000 ppm of amoxicillin E = - 0.560 V on the 7th day. When inserted amoxicillin to WO4-2 concentrations were the best for 1000, 2000 and 3000 ppm of amoxicillin inserted in 0.07 mol/L Na2WO4 obtaining the 7th day of immersion values respectively E = - 0.380 V, E = -0.400 V and E = - 0370 V. As for the coatings based on cellulose acetate showed no significant potential values, getting around E = -0.645 V to day 7. When inserted amoxicillin 2000 ppm and 0.07 mol/L of Na2WO4 the film 5 % remained stable potential shift, 2) It is demonstrated that EIS to 0.07 mol/L of Na2WO4 resistance values increased significantly than other inhibitors, 3) and the anodic polarization curves showed that for 0.07 mol/L of the Na2WO4 potential breakup film (ERP) possessed more positive values, ERP = +0.07 V when compared with the other inhibitors.